The Aurora of Mental Health. An Contribution from the Anthropology of Psychiatric Care - Miguel Ángel Piñeiro Groba (Universidad de Alicante, 2018)
In this review we describe the characteristics of mental care in pre-industrial cultures from an anthropological perspective that allows us to open this complex theme to new perspectives and interpretations.